Non-TAL Effectors From Xanthomonas oryzae pv. oryzae Suppress Peptidoglycan-Triggered MAPK Activation in Rice - Long, Juying; Song, Congfeng; Yan, Fang; Zhou, Junhui; Zhou, Huanbin; Yang, Bing (Frontiers in Plant Science, 2018)
Xanthomonas oryzae pv. oryzae, the causal bacterial pathogen of bacterial blight of rice, depends on its type III secretion system and associated effector proteins to grow and colonize the vascular tissues of rice plants. The type III effectors include a family of closely related transcription activator-like (TAL) effectors and the rest of diverse effectors, so-called non-TAL effectors. Our understanding of non-TAL effectors for pathogenesis in rice blight is still limited. Here we report the activation of mitogen-activated protein kinase pathway in rice cells by the X. o. pv. oryaze derived peptidoglycan. Amongst 17 non-TAL effectors transiently expressed in rice cells, we found that 3 effectors (XopZ, XopN, and XopV) were able to suppress the peptidoglycan-triggered MAPK activation. The triple mutant of the X. o. pv. oryzae strain PXO99A with XopZ, XopN and XopV inactivated showed additively reduced virulence. Our results demonstrate the collective and redundant ability of defense suppression by the non-TAL effectors in causing bacterial blight of rice.